KLASIFIKASI MAK.AN AN TRADISIONAL DI PERHOTELAN - Sukana Sabudi, I Nyoman (Pusat penelitian & Pengabdian Kepada Masyarakat STP Nusa Dua Bali, 2011)
The aim of the present study was to classify and to investigate the reasons for the clasification of Balinese traditional foods in hotels and restaurants in Nusa Dua Resorts Area. The study was conducted using data of the number and types of Balinese traditional foods served in hotels and restaurants and guests 'perception towards Balinese food. The study found out that the Balinese food could be classified based on: the types of ingridients, methods of cooking, how the food were served (hot, ';JClrm, cold), and the product or the thikness of the food.